HRV and blood parameters for assessing the physiological functioning of cyclists during long-distance rides across different altitudes - Du, Weiping; Zhang, Ming; Niu, Xiaodan; Li, Hao; Wan, Yimin (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to systematically investigate the changes and interrelationships between heart rate variability (HRV) and hematological parameters in cyclists during prolonged exposure to varying altitudes, in order to reveal the dynamic interplay between autonomic nervous system regulation and hematological adaptation.MethodsSeventeen cycling enthusiasts aged 16–25 years participated in an 8-day altitude cycling challenge. HRV and hematological parameters were measured at three altitudes: 485 m, 1,627 m, and 4,182 m.ResultsHematological parameters, including white blood cell count (WBC), hemoglobin concentration (HGB), hematocrit (HCT), mean corpuscular hemoglobin concentration (MCHC), platelet count (PLT), and plateletcrit (PCT), significantly increased at both 1,627 m and 4,182 m (P < 0.05). Physiological measures such as heart rate (HR), systolic blood pressure (SBP), and diastolic blood pressure (DBP) showed significant elevations at 4,182 m (P < 0.05), while vital capacity (VC) significantly decreased (P < 0.05). HRV time-domain indices, including the standard deviation of R–R intervals (SDNN) and the root mean square of successive R–R interval differences (RMSSD), significantly increased at 1,627 m (P < 0.05) but decreased at 4,182 m (P < 0.05). Frequency-domain indices, including very low-frequency power (VLF), low-frequency power (LF), and high-frequency power (HF), significantly decreased at 4,182 m (P < 0.01). Among nonlinear HRV metrics, the short-term standard deviation of the Poincaré plot (SD1) and long-term standard deviation (SD2) significantly decreased at 4,182 m (P < 0.01), while approximate entropy (ApEn), sample entropy (SampEn), and alpha2 significantly increased (P < 0.05). Correlation analysis revealed that at 485 m, SDNN was negatively correlated with HCT (r = −0.55, P < 0.05) and PLT (r = −0.50, P < 0.05), while LF and HF were negatively correlated with HCT (r = −0.55 and −0.54, P < 0.05). At 1,627 m, SDNN was positively correlated with MCV (r = 0.53, P < 0.05), LF with MCV (r = 0.23, P < 0.05), and LF/HF was negatively correlated with MCHC (r = −0.52, P < 0.05). At 4,182 m, SDNN was positively correlated with MCHC (r = 0.51, P < 0.05), VLF was negatively correlated with WBC (r = −0.63, P < 0.05), ApEn was positively correlated with both WBC (r = 0.76, P < 0.05) and HCT (r = 0.62, P < 0.05), and SampEn was positively correlated with WBC (r = 0.74, P < 0.05).ConclusionThis study systematically evaluated the dynamic changes in HRV and hematological parameters in cyclists during prolonged exposure to different altitudes. The results showed that at moderate altitude, athletes exhibited a coordinated response of enhanced short-term autonomic adaptation and increased red blood cell volume. At very high altitude, HRV decreased overall while its complexity increased, indicating a stress-compensatory mechanism dominated by sympathetic activation. Altitude-specific correlations between HRV and blood parameters suggest a potential interplay between autonomic regulation and hematological adaptation.